Pengaruh Budaya Kerja dan Komitmen Organisasi Terhadap Produktivitas Karyawan PT Pelindo (Persero) Cabang Samarinda (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of work culture and organizational commitment on employee productivity at PT PELINDO (Persero) Samarinda Branch. The background of this research is based on the important role of human resources in increasing the efficiency and competitiveness of port service companies. The method used is a quantitative approach with survey techniques using questionnaires to 62 employees as respondents. The regression analysis results show that work culture has a positive and significant effect on employee productivity, while organizational commitment has no significant effect when tested partially. However, simultaneously, both variables have a significant effect on productivity with a contribution of 61.9%. This finding confirms the importance of implementing a strong work culture and the need to strengthen organizational commitment as a human resource management strategy. The implications of this study provide practical input for company management to focus on developing work culture values and building employee emotional attachment to support the achievement of optimal productivity